Prototype development of vehicle collision avoidance system using Arduino - Gunawan, Teddy Surya; Omar, Arifah; Kartiwi, Mira; Effendi, Mufid Ridlo; Ismail, Nanang (IEEE, 2021)
This paper focused on the prototype development of a vehicle collision avoidance system (VCAS) using Arduino and Global Positioning System (GPS). Advanced systems for collision detection and new avoidance safety system are terms which one would expect to see together. The proposed method prevents vehicle collision in a forward collision and straight road. Furthermore, the proposed system can generate a collision warning alarm when a car meets an emergency event, and during that time, drivers should take appropriate action. The proposed system used ultrasonic sensors as ranging components to get the nearby distance of the host car. Next, this system also used GPS to provide the geographical position and speed of the host car precisely. From the speed data, acceleration can be calculated. Thus, from all of these inputs data, the braking distance can be determined. If the following distance was lesser than the braking distance, a warning system was issued, or assisted braking was performed. Experimental results showed that the system works well on a pedestrian walkway with a soft surface compared to a paved road with a rough surface. However, the GPS accuracy was affected by the noise from the surrounding buildings, which requires position data preprocessing.